Coastal resource-environmental carrying capacity assessment: A comprehensive and trade-off analysis of the case study in Jiangsu coastal zone, eastern China. (15th March 2020) - Liu, Rongjuan; Pu, Lijie; Zhu, Ming; Huang, Sihua; Jiang, Yu
Abstract: The coastal zone is the key area for sustainable scientific research and realizing the strategic development of China's economic and ecological goals. As one of the regions with the highest human activity, the coordinated development of its ecological environment and social economy cannot be ignored. Based on the study of the relationship between ecological environment quality and socio-economic development, this paper proposed the Coastal Resource-environmental Carrying Capacity (CRECC) which including three subsystems (the Resource's system, the Ecological system, and the Socio-economical system), as well as 6 first-level indices and 20 s-level indicators. The entropy weight method and analytic hierarchy process were used to calculate the average weight, and the changing rate of carrying capacity value was analyzed based on the ordinary least square method. Taking the coastal zone of Jiangsu Province as the study area, we calculated the changes of comprehensive/subsystems' carrying capacity from 2000 to 2015, and the trade-off relationship within the subsystem was analyzed. From 2000 to 2015, the value of CRECC, the Resource's system, and the Socio-economical system decreased while the Ecological system's value showed a volatility rise. Overall, the regional carrying capacity level was low. However, positive environmental management measures have significantly improved the status of the ecological environment and helped to alleviate the environmental pressure brought by population growth. the Ecological system played an important role in the change of regional carrying capacity. Vegetation coverage, coastal water environment quality index, tidal flat reclamation area, habitat, and ecological land proportion are significant influencing factors. This also indicated that the landscape ecological status, offshore water quality and utilization of space resources in Jiangsu coastal zone aren't sustainable. Therefore, it is recommended to improve the ecological resilience of coastal zones, such as implementing spatial planning of tidal flat resources, and controlling pollutant discharge, etc. in order to promote the regional sustainable development. Graphical abstract: Image 1 Highlights: We developed an evaluation index system to assess the carrying capacity of coastal environment. The trade-off within subsystems was considered when setting up the evaluation system. The approach helps promote the rational allocation of resources utilization and optimization of coastal management.